A thermodynamics description of the system with N massive parallel rigid wires - Kokubun, Fernando [UNESP] (IOP Publishing, 1996)
In this work, the behaviour of the system with N massive parallel rigid wires is analysed. The aim is to explore its resemblance to a system of multiple cosmic strings. Assuming that it behaves like a 'gas' of massive rigid wires, we use a thermodynamics approach to describe this system. We obtain a constraint relating the linear mass density of the massive wires, the number of the massive wires in the system and the dispersion velocity of the system. © 1996 IOP Publishing Ltd.